Relationship between β1-AA and AT1-AA and Cardiac Function in Patients with Hypertension Complicated with Left Ventricular Diastolic Function Limitation - Liang Wang; Xue-Bai Lv; Yu-Ting Yuan; Ning Wang; Hong-Ying Yao; Wen-Chao Zhang; Peng-Fei Yin; Xiao-Hui Liu (Hindawi-Wiley, 2023)
Objective. To investigate the association between β1 adrenergic receptor autoantibodies (β1-AA) and angiotensin II type-1 receptor autoantibodies (AT1-AA) and cardiac function in patients with hypertension complicated with left ventricular diastolic function limitation. Methods. A total of 120 patients with essential hypertension who were not taking drug treatment and were hospitalised in the Department of Cardiology at the authors' hospital from April 2018 to December 2018 were enrolled in this study and divided into a diastolic dysfunction group (65 cases) and a normal diastolic group (55 cases) according to their left ventricular diastolic function. The levels of cardiac parameters, β1-AA, AT1-AA, and other indicators were compared. Logistic regression analysis was used to analyse the related factors affecting left ventricular diastolic dysfunction (LVDD). The diagnostic efficacy of related factors in the diagnosis of diastolic dysfunction was evaluated. Results. Univariate analysis demonstrated that the left ventricular posterior wall diameter (10.29±1.23 vs. 9.12±1.53), left ventricular systolic dysfunction (10.56±1.37 vs. 9.43±1.44), systolic blood pressure (152.37±10.24 vs. 140.33±5.99), diastolic blood pressure (95.66±6.34 vs. 87.33±7.28), β1-AA (33 vs. 9 cases), and AT1-AA (35 cases vs. 12 cases) were higher in the dysfunction group than in the control group (all P<0.05). Multivariate regression analysis showed that β1-AA (odds ratio OR=1.96, 95% confidence interval CI: 1.369-4.345) and AT1-AA (OR=2.02, 95% CI: 1.332-6.720) were independent risk factors for cardiac diastolic dysfunction (P<0.05). Both autoimmune antibodies had a certain predictive value, and the combined prediction value of the two was the highest, with an area under the curve of 0.942 (95% CI: 0.881~0.985). Conclusion. The positive rate of β1-AA and AT1-AA in essential hypertension patients with LVDD was higher than that in the normal group. Both β1-AA and AT1-AA could be used as early markers of LVDD in essential hypertension patients.